2015
DOI: 10.1111/cid.12357
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of a Single Dose of Amoxicillin on the Oral Microbiota

Abstract: A single dose given as prophylaxis to prevent a surgical-site infection results in a significant reducing effect on the oral streptococcal microflora in the gingival crevice and may have an impact on bacteria spreading into tissues and the bacteremia of streptococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…However, previous report indicated that bacterial composition of the salivary microbiota was stable against antibiotic treatment compared to feces microbiota, and impacts of antibiotics including ciprofloxacin, amoxicillin, and minocycline on the salivary microbiota composition were lost by 1 week to 1 month post-exposure (Zaura et al, 2015). Another report also suggested the impact of amoxicillin on salivary bacteria peaked out 4 h after exposure (Larsson Wexell et al, 2016). In this study, the pre-and post-treatment sampling were performed on an average of 26.5 ± 9.9 and 18.6 ± 9.3 days after antibiotics exposure, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…However, previous report indicated that bacterial composition of the salivary microbiota was stable against antibiotic treatment compared to feces microbiota, and impacts of antibiotics including ciprofloxacin, amoxicillin, and minocycline on the salivary microbiota composition were lost by 1 week to 1 month post-exposure (Zaura et al, 2015). Another report also suggested the impact of amoxicillin on salivary bacteria peaked out 4 h after exposure (Larsson Wexell et al, 2016). In this study, the pre-and post-treatment sampling were performed on an average of 26.5 ± 9.9 and 18.6 ± 9.3 days after antibiotics exposure, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Prospective cohort studies revealed that Shannon biodiversity index was decreased during amoxicillin treatment and was subject to further reduction in the following 6 months’ time period ( Menon et al, 2019 ; Monroy-Pérez et al, 2020 ; Nel Van Zyl et al, 2022 ). The density of Neisseria, Streptococcus and Veillonella strains in the oral cavity was also reported to decrease during treatment with amoxicillin ( Larsson Wexell et al, 2016 ; Moraes et al, 2020 ). Save commonly used amoxicillin, other groups of antibiotics with various mechanisms of action can influence the oral microbiota and promote the selection of multi-drug resistant strains and their horizontal transmission ( Zaura et al, 2015 ; Moraes et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, nearly all of the patients enrolled in this study received antibiotics at the time of intubation and a single dose of antibiotics has been shown to alter the microbiome of other body compartments and may impact our ability to evaluate the lower airways microbiome via tracheal aspirates. 40 , 41 Fifth, tracheal aspirates specimens may not adequately reflect lower lung bacteria. However, other methods such bronchiolar alveolar lavage are not frequently performed in children.…”
Section: Discussionmentioning
confidence: 99%